Peak bodies: Indigenous representation in the Australian higher education sector. Issue 1 (April 2022) - Trudgett, Michelle; Page, Susan; Coates, Stacey K
The number of Indigenous Australians engaged in the higher education has risen steadily in recent years. Since the 1970s, several groups have been established to represent issues impacting Indigenous staff and students across the Australian higher education sector. Despite the deep passion and commitment by Indigenous leaders to advance Indigenous education in general, no single group currently provides adequate representation and advocacy on these issues. This article reports on findings from an Australian Research Council-funded study on Indigenous leadership in higher education. In doing so, it shares the perspectives of senior Indigenous leaders, university executive such as Vice-Chancellors and Indigenous academics. Ultimately, this article purports that it is necessary for the Federal Government and Universities Australia to work collaboratively with Indigenous People if we are going to see collective advancement across the sector and that this needs to occur in a more meaningful way than currently exercised.